Anaplastic lymphoma kinase-special immunity and immunotherapy - Guo, Ye; Guo, Hanfei; Zhang, Yongfei; Cui, Jiuwei (Frontiers in Immunology, 2022)
Alterations in the anaplastic lymphoma kinase (ALK) gene play a key role in the development of various human tumors, and targeted therapy has transformed the treatment paradigm for these oncogene-driven tumors. However, primary or acquired resistance remains a challenge. ALK gene variants (such as gene rearrangements and mutations) also play a key role in the tumor immune microenvironment. Immunotherapy targeting the ALK gene has potential clinical applications. Here, we review the results of recent studies on the immunological relevance of ALK-altered tumors, which provides important insights into the development of tumor immunotherapies targeting this large class of tumors.